Saamelaiskielten verbijohdostyyppien historiasta ja variaatiosta - Kuokkala, Juha (Helsingin yliopisto, 2023)
This dissertation examines the distribution and variation of certain derivational verb types in the Saami languages and, on the basis of that, assesses the historical background of the verb types. The study is based on extensive lexical material covering the whole Saami language area. The verbs belonging to each derivational type have been gathered from the material, and their likely base words or derivational correlates have been identified. A key objective of the investigation is to determine how the derivational types can be divided into subtypes based on the semantics on the one hand and the morphotaxis on the other, that is, what kind of bases the derivational suffixes attach to and what kind of morphophonological alternations they trigger in the base and at the border of the base and the suffix. A further objective is to determine the frequencies of each derivational type and subtype in the data from different Saami languages and pinpoint the areal distributions of single derivatives. The quantitative data on type frequencies should be taken as indicative, since the base material varies greatly from one Saami language to another in terms of both quantity and quality. The dissertation consists of five original publications and a concluding chapter. The first two publications examine inchoative derivatives, in other words, derivatives denoting the beginning of the action indicated by the base verb. For the most widely used Saami inchoative suffix *-koatē- (North Saami -goahtit) and its longer variant *-(č/š)koatē- (North Saami -šgoahtit), the connections to Veps and Mordvin inchoative suffixes suggested in previous scholarship are shown to be unlikely, and it is argued that the *-koatē- suffix instead has its origin in the lexical verb *poatē- (North Saami boahtit ‘to come’). The initial consonant č/š in the longer suffix variant, then, is shown to descend from the frequentative suffix *-(e̮)kče̮-, which still occurs as an independent inchoative suffix -ahtja- ~ -áhtja- in the western Saami languages. ...